Global effect of COVID-19 pandemic on the rate of acute coronary syndrome admissions: a comprehensive review of published literature - Ayman Helal; Lamis Shahin; Mahmoud Abdelsalam; Mokhtar Ibrahim (Open Heart)
Background The COVID-19 pandemic has disrupted healthcare systems across the world. The rate of acute coronary syndrome (ACS) admissions during the pandemic has varied significantly.Objectives The purpose of this study is to investigate the effect of the pandemic on ACS hospital admissions and to determine whether this is related to the number of COVID-19 cases in each country.Method Search engines including PubMed, Embase, Ovid and Google Scholar were searched from December 2019 to the 15 September 2020 to identify studies reporting ACS admission data during COVID-19 pandemic months in 2020 compared with 2019 admissions.Results A total of 40 studies were included in this multistudy analysis. They demonstrated a 28.1% reduction in the rate of admission with ACS during the COVID-19 pandemic period compared with the same period in 2019 (total of 28 613 patients in 2020 vs 39 225 in 2019). There was a significant correlation between the absolute risk reduction in the total number of ACS cases and the number of COVID-19 cases per 100 000 population (Pearson correlation=0.361 (p=0.028)). However, the correlation was not significant for each of the ACS subgroups: non-ST-elevation myocardial infarction (STEMI) (p=0.508), STEMI (p=0883) and unstable angina (p=0.175).Conclusion There was a significant reduction in the rate of ACS admission during the COVID-19 pandemic period compared with the same period in 2019 with a significant correlation with COVID-19 prevalence.